A study on customer awareness towards seaweed products in Kota Kinabalu town / Azmy Asis - Asis, Azmy (2008)
Inno Fisheries Sdn. Bhd should focus more in the marketing strategy to create awareness and acceptance among their potential customers especially in Kota Kinabalu city area and in order of their existing customers stay loyal to buy and consume their products. By concentrate in creating awareness and acceptance among customers, the company should produce desire result to be excellent in marketing strategy. Company should be emphasizing more on the marketing strategy in order to be able to compete among their competitors. In addition, this study mainly purposes to identify the company existing customer awareness and acceptance towards company products. This study included Inno Fisheries Sdn. Bhd. Existing customers in Kota Kinabalu area only and not covered outside the town area. The target population is in this study are 50 respondents.